Ethnic Attitudes and Prejudice within the System of Multicultural Education - Kovačikova, Dagmar (Communications - Scientific letters of the University of Zilina, 2007)
In the process of multicultural education and reaching its humane objective we often hit the barrier of prejudice. In order to reduce prejudice it is necessary to be aware of the fact that it means a long-term influence by which prejudice can be at least reduced, if not completely eliminated. Negative attitudes or even prejudices at the point of meeting of two different ethnic groups can also be seen among children. The area of ethnic and racial attitudes was the subject of survey, in which we examined positive or negative opinions of the elementary school pupils concerning selected ethnic and racial groups they can get in contact with.